ВПЛИВ СТУПЕНЯ ЗАКРІПЛЕННЯ ОБМОТКИ В ТОРЦІ ПАЗА СТАТОРА ТУРБОГЕНЕРАТОРА НА ТЕРМОМЕХАНІЧНІ ХАРАКТЕРИСТИКИ ІЗОЛЯЦІЇ ЇЇ СТЕРЖНЯ - Кучинський, К.A. (Інститут електродинаміки Національної академії наук України, 2022)
Based on the finite element method, a numerical method for calculating thermomechanical movements and stresses of the components of the stator winding of a powerful turbogenerator is proposed, taking into account its regime and structural factors. The results of studies of these characteristics in insulation along the length of the core in radial and axial directions in different variants of fixing the winding in the end zone of the core are presented. The regularities of distribution of maximum and average values of thermomechanical parameters in the groove and frontal parts with the traditional method of fastening and the presence of a free section of the core in the end zone of the stator in the nominal mode of operation of the generator are determined. Ref. 12, fig. 4.